Vegetation diversity, structure and composition in nature-based recreation sites as a potential tourist attraction in Banyuwangi, Indonesia - LAILA NUR HABIBAH; LUCHMAN HAKIM; EDRIANA PANGESTUTI; DIAN SISWANTO; BRIAN RAHARDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Habibah LN, Hakim L, Pangestuti E, Siswanto D, Rahardi B. 2024. Vegetation diversity, structure and composition in nature-based recreation sites as a potential tourist attraction in Banyuwangi, Indonesia. Biodiversitas 25: 3273-3285. The presence of vegetation in nature-based tourism sites plays an important role in adding natural scenic beauty and creating comfortable local climates. However, the potential of vegetation in the recreation landscape for conservation and educational aspects is less studied. This research aims to identify vegetation diversity, structure and composition of plant species in nature-based tourism recreation sites in Banyuwangi District, East Java. Vegetation survey was conducted at 16 recreation sites, ranging from coastal to lower mountain ecosystems with varying management types from national parks, state and privately owned enterprises and community-private ownerships. Research shows that recreation sites contain diverse plant species that can support nature-based tourism attractions. The recreation sites in the national parks harbor native vegetation in, which it is important for biodiversity education through nature-based tourism programs. Fewer exotic plant species are found in nature-based recreation sites, especially in conservation areas. Conversely, nature-based recreation sites managed by community and private are dominated by exotic plant species. The existence of exotic plant species in nature-based recreation sites can add economic value by providing agrotourism activities, yet it requires special attention to protect the native habitats in those sites.